Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.